SAT0640 Whole body-mri in axial spondyloarthritis (AXSPA): diffusion weighted imaging (DWI) outperforms the stir sequence. (12th June 2018) - Nzeusseu Toukap, A.; Vander Maren, N.; Collette, L.; Michoux, N.; Triqueneaux, P.; Stoenoiu, M.S.; Houssiau, F.; Malghem, J.; Lecouvet, F.E.
Abstract : Background: None Objectives: To compare the diagnostic value of DWI and STIR sequences as part of WB-MRI studies in AxSpA patients. Methods: 20 consecutive patients (P) with confirmed diagnosis of active AxSpA and 20 controls (C) referred for metastatic cancer screening were investigated with identical WB-MRI protocols including DWI and STIR images. Two independent observers recorded the presence of "lesions" (high signal intensity foci on STIR and high b-value DWI images) in 17 anatomic areas; making a 17-point "area score") and a calculated 40-point "lesion score". Both were tested for correlation with clinical and biological parameters. Results: In P, the "lesion score" was significantly higher with DWI than with STIR (p<0.025). The most experienced observer had higher DWI lesion scores, suggesting a learning effect. The lesion score and some anatomic areas could discriminate P from C. For this purpose, DWI had a higher AUC than STIR (AUC=99.9, CI: 99.5–1.00 vs AUC=95.8, CI: 90.9–1.00). For a trained MRI observer using DWI, a lesion score threshold of >4 had 100% sensitivity and 95% specificity. With STIR, a threshold of >3 had 85% sensitivity and 90% specificity. The area score AUC was significantly lower with STIR than with DWI (p=0.0233), but no satisfactory area score threshold was identified. The most frequently involved areas were the spine and hip entheses in C, the spine and SIJ in P. Manubrio- and chondro-sternal joint involvement was specific for AxSpA. The lesion score was positively correlated with ASDAS-CRP and (log) CRP. Conclusions: DWI is a promising alternative to STIR in WB-MRI studies for the detection of active lesions in AxSpA. Training may be necessary. The involvement of specific anatomic areas could distinguish P from C. Acknowledgements: None Disclosure of Interest: None declared